Sustainable microalgae‐based palm oil mill effluent treatment process with simultaneous biomass production. (5th August 2016) - Halim, Fatimah T. A.; Guo, Xiaoyi; Su, Gaomin; Ngee, Hannah L.; Zeng, Xianhai; He, Ning; Lin, Lu; Danquah, Michael K.
Abstract : The production of copious quantities of waste palm oil mill effluent (POME) is an unavoidable consequence of palm oil industries, and requires effective treatment before discharge into the environment. Microalgae possess a significant nutrient bio‐sorption capacity in addition to high photosynthetic and carbon bio‐sequestration rates, and hence can be exploited for sustainable POME treatment operations. Bioprocess research on the use of microalgal cells to remove specific chemical species from POME is limited. This work investigated the application of the microalgae Chlorella vulgaris and Nannochloropsis sp. for nitrogen and phosphorus removal from POME with simultaneous biomass production. Both microalgae species displayed maximum total nitrogen and phosphorus removal efficiencies at 50 % POME concentration within 8 days. Studies on nitrogen and phosphorous addition demonstrated that a N/P molar ratio of 10:1 improved biomass accumulation with 90.0 % nitrogen and 82.1 % phosphorus removals. These results showed that high treatment efficiencies can be obtained using C. vulgaris and Nannochloropsis sp. for applications in industrial POME treatment.